2022
DOI: 10.1021/acssuschemeng.2c01375
|View full text |Cite
|
Sign up to set email alerts
|

Data-Centric Development of Lignin Structure–Solubility Relationships in Deep Eutectic Solvents Using Molecular Simulations

Abstract: Lignin is a natural source of aromatic chemicals with significant potential as an abundant, renewable feedstock for value-added products. Deep eutectic solvents (DES)�solvents composed of a hydrogen bond donor (HBD) and acceptor (HBA) in varying ratios�have emerged as a highly tunable class of solvents for lignin solubilization. However, the variety of possible DES compositions and limited molecular-scale understanding of lignin solubility makes solvent selection a challenge without laborious trial-and-error e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…Finally, we envision further expanding the database to consider new classes of green or designer solvents with potential value in polymer dissolution, such as ionic liquids or deep eutectic solvents. 62,63…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we envision further expanding the database to consider new classes of green or designer solvents with potential value in polymer dissolution, such as ionic liquids or deep eutectic solvents. 62,63…”
Section: Discussionmentioning
confidence: 99%
“…Future work will investigate variations in molecular weight and how this influences predictions. Similarly, future work will extend this approach more explicitly to solvent mixtures, particularly for ionic liquids or deep eutectic solvents, to explore whether preferential solvation effects manifest in these systems, which may not be captured by our current framework and may require additional descriptors to quantify. ,,, …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used empirical parameters, such as Hansen solubility parameters, to guide solvent selection for fractionation, but these parameters do not capture variations in lignin composition. Recent computational studies using conductor-like screening model for realistic solvents (COSMO-RS) calculations or molecular dynamics (MD) simulations have also explored the molecular basis of lignin solubility but generally for a small range of lignin structures/solvents due to their computational expense. There, thus, remains a need for methods to efficiently guide solvent selection for lignin solubilization while accounting for the heterogeneous population of possible lignin structures.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the minimal size representing the actual size becomes important for calculating thermodynamic parameters 21 . It has been shown that the solubility parameter (δ) and density of polymers stabilize and converge to a constant value with the increasing molecular chain length 13,18,22 . The solubility parameter (δ) and density of NR and BR at different molecular weights need to be calculated to determine the minimum size.…”
Section: Methodsmentioning
confidence: 99%
“…21 It has been shown that the solubility parameter (δ) and density of polymers stabilize and converge to a constant value with the increasing molecular chain length. 13,18,22 The solubility parameter (δ) and density of NR and BR at different molecular weights need to be calculated to determine the minimum size. Figure 2 shows the relationship of repeating units and the solubility parameter and density.…”
Section: Simulationmentioning
confidence: 99%